PATHOGENIC MICROORGANISMS ASSOCIATED WITH PERIODONTAL DISEASE IN INDIVIDUALS WITH TYPE 2 DIABETES - Mihaela Mariș; Sorana Maria Bucur; Mariș Marius; Mariana Păcurar; Kamel Earar (Romanian Journal of Oral Rehabilitation)
This study examined the presence of periodontal pathogens in 29 patients with type 2 diabetes, categorized into three age groups: Group I (18–30 years), Group II (31–50 years), and Group III (51+ years). Porphyromonas gingivalis was detected in various degrees across all groups, with no significant correlation between pathogen presence and patient age. The study also highlighted the prevalence of Aggregatibacter actinomycetemcomitans, Bacteroides forsythus/Tannerella forsythia, and Fuzobacterium nucleatum, which were present in 29 patients, indicating a strong association with periodontal disease. Additionally, Eikenella corrodens and Capnocytophaga were found in patients with hyperglycemia, with positive results more frequent in Group II. Less common pathogens, including Treponema denticola, Prevotella intermedia, and Campylobacter rectus, were detected in smaller numbers, but their presence suggests a significant role in periodontal pathology, particularly in older patients. These findings reinforce the link between oral microbial agents and periodontal disease in patients with type 2 diabetes. Effective oral hygiene and periodontal treatment are essential in reducing pathogen load and improving glycemic control, potentially lowering the risk of systemic complications such as cardiovascular disease.